Kebijakan Penyelesaian Perkara Kekerasan Seksual Terhadap Anak - Usmany, Jesisca Gloria; Sopacua, Margie Gladis; Saimima, Judy Marria (PATTIMURA Law Study Review, 2024)
ABSTRACT: Children are the greatest gift for the family, religion, nation and state. children are the successors of ideals for the progress of the nation, and for that children need protection. Children are often used as material for violence by adults without thinking about the impact of these actions, one of these violence is sexual violence. Sexual violence is an act or behavior that is carried out by targeting a person's sexuality or sexual organs without consent, with elements of threat and coercion, for this reason children must be given protection and provide appropriate sanctions for those who commit this act. This research is empirical juridical research, which uses a statutory approach, conceptual approach, and case approach, the legal materials used are primary, secondary and tertiary legal materials. The results of the discussion of this paper are to explain the factors that influence or cause the occurrence of criminal acts of sexual violence against children, namely internal factors containing intentions and desires that come from within, lust, sexual deviations, and gaps in power and violence. external factors or those that come from outside themselves where the contents are in the form of conditions and the environment where sexual violence crimes are committed and the influence of the social environment where the perpetrator lives besides that this research also explains the efforts made to overcome sexual violence against children, namely through penal and non-penal channels. The penal path is a settlement path using repressive criminal law. Then for the non-penal path is a solution path outside of preventive criminal law.